Explaining the variability in cardiovascular risk factors among First Nations communities in Canada: a population-based study. Issue 12 (December 2019) - Anand, Sonia S; Abonyi, Sylvia; Arbour, Laura; Balasubramanian, Kumar; Brook, Jeffrey; Castleden, Heather; Chrisjohn, Vicky; Cornelius, Ida; Davis, Albertha Darlene; Desai, Dipika; de Souza, Russell J; Friedrich, Matthias G; et al.
Summary: Background: Historical, colonial, and racist policies continue to influence the health of Indigenous people, and they continue to have higher rates of chronic diseases and reduced life expectancy compared with non-Indigenous people. We determined factors accounting for variations in cardiovascular risk factors among First Nations communities in Canada. Methods: Men and women (n=1302) aged 18 years or older from eight First Nations communities participated in a population-based study. Questionnaires, physical measures, blood samples, MRI of preclinical vascular disease, and community audits were collected. In this cross-sectional analysis, the main outcome was the INTERHEART risk score, a measure of cardiovascular risk factor burden. A multivariable model was developed to explain the variations in INTERHEART risk score among communities. The secondary outcome was MRI-detected carotid wall volume, a measure of subclinical atherosclerosis. Findings: The mean INTERHEART risk score of all communities was 17·2 (SE 0·2), and more than 85% of individuals had a risk score in the moderate to high risk range. Subclinical atherosclerosis increased significantly across risk score categories (p<0·0001). Socioeconomic advantage (–1·4 score, 95% CI −2·5 to −0·3; p=0·01), trust between neighbours (–0·7, −1·2 to −0·3; p=0·003), higher education level (–1·9, −2·9 to −0·8, p<0·001), and higher social support (–1·1, −2·0 to −0·2; p=0·02) were independently associated with a lower INTERHEART risk score; difficulty accessing routine health care (2·2, 0·3 to 4·1, p=0·02), taking prescription medication (3·5, 2·8 to 4·3; p<0·001), and inability to afford prescription medications (1·5, 0·5 to 2·6; p=0·003) were associated with a higher INTERHEART risk score. Collectively, these factors explained 28% variation in the cardiac risk score among communities. Communities with higher socioeconomic advantage and greater trust, and individuals with higher education and social support, had a lower INTERHEART risk score. Communities with difficulty accessing health care, and individuals taking or unable to afford prescription medications, had a higher INTERHEART risk score. Interpretation: Cardiac risk factors are lower in communities with high socioeconomic advantage, greater trust, social support and educational opportunities, and higher where it is difficult to access health care or afford prescription medications. Strategies to optimise the protective factors and reduce barriers to health care in First Nations communities might contribute to improved health and wellbeing. Funding: Heart and Stroke Foundation of Canada, Canadian Partnership Against Cancer, Canadian Institutes for Health Research.